2022
DOI: 10.1186/s13052-022-01328-0
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypothyroidism after newborn screening program reorganization in the Apulia region

Abstract: Background Congenital hypothyroidism (CH) is the most frequent congenital endocrine disorder. The purpose of the present study was to evaluate the incidence and etiological classification of CH in Apulia in a three-year period according to the reorganization of the regional screening program in a single central laboratory, as well as to analyze the growth characteristics and the associated risk factors of the CH newborns diagnosed during the study period. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A study of births in Piedmont indicated that their current two-screen protocol for all newborns was sufficient [ 873 ]. In the Apulia region, relocation of the screening laboratory to a more central location has also been shown to improve clinical care for CH through more timely initiation of treatment and improved case management [ 874 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study of births in Piedmont indicated that their current two-screen protocol for all newborns was sufficient [ 873 ]. In the Apulia region, relocation of the screening laboratory to a more central location has also been shown to improve clinical care for CH through more timely initiation of treatment and improved case management [ 874 ].…”
Section: Resultsmentioning
confidence: 99%
“…High recall rates represent higher costs for screening programs, in addition to a higher number of healthy children undergoing needless exams and appointments, with a relevant emotional impact for the patients and their families. The recall rate increased in all reported programs that implemented a reduction in the cut-off screening [30,31], up to 10 times [24,32].…”
Section: Discussionmentioning
confidence: 99%
“…A similar reduction, from 10 to 6 mIU/L in the United Kingdom, led the recall rate to increase from 0.08% to 0.23% [ 12 ]. The recall rate increased in all reported programs that implemented a reduction in the cut-off screening [ 30 , 31 ], up to 10 times [ 24 , 32 ]. High recall rates represent higher costs for screening programs, in addition to a higher number of healthy children undergoing needless exams and appointments, with a relevant emotional impact for the patients and their families.…”
Section: Discussionmentioning
confidence: 99%